Population of Hammerhead Sharks at the Fish Landing Port (PPI) of Meulaboh, West Aceh District (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2022)
The territorial waters of West Aceh, Aceh Province is an area with a long topography and wide sea. The water area is included in the Republic of Indonesia State Fisheries Management Area (WPPNRI) 572. The hammerhead shark Sphyrna lewini is not significantly different from the hammerhead shark Sphyrna mokarran, both of which are characterized by their heads widening laterally and being less than a third of their body shape. Sphyrna lewini has a body size ranging from 50 cm to 420 cm, which generally lives in the tropics and is easily found in island waters with a continental shelf reaching a depth of 275 m. Its important role can be seen from an ecological perspective in the development of conservation and sustainable marine and fishery resources. This should be managed responsibly for the sake of creating a prosperous and independent society. West Aceh district is a coastal area that is rich in fishery products. This is inseparable from its location directly facing the Indian Ocean which is rich in fish. However, the sustainability of the hammerhead shark is not yet known in detail. Therefore, a study on the sustainability of hammerhead sharks at PPI Meulaboh needs to be carried out. The method used in this study was a field experiment (experimental fishing) from fishermen’s catches. Furthermore, the data obtained were tabulated and analyzed. Overall, the size of the hammerhead shark caught by fishermen was in the interval of 62.5-93.5 cm. By sex, there were 19 male sharks and 20 female sharks. The maximum length (L∞) was 96 cm. Furthermore, the value of K was 0.290 per year. The Von Bertanlffy growth equation model was Lt = 91.6(1-e-0.29(t+0.03)). The value of total mortality (Z) was 0.84 and natural mortality (M) was 0.94 with a temperature of 29 0C, where the incidence of natural deaths was greater than fishing deaths. Fishing mortality (F) was 0.10, with an exploitation ratio (E) was of 0.12.
Keywords: Hammerhead shark, Meulaboh, population, Sphyrna lewini.